Accountability of the Sharia Supervisory Board (DPS) in Managing Sharia Accommodation Based on DSN-MUI Fatwa No. 108 of 2016 on Sharia Tourism (Case Study: Sharia Hotels in Medan City) - Dhio Bagus Setya; Fatimah Zahara (Journal Equity of Law and Governance, 2024)
This study aims to analyze the accountability/responsibility of the Sharia Supervisory Board (DPS) in overseeing the operations of Sharia accommodations, with a specific focus on Sharia hotels in Medan City. The primary question addressed in this research is how the DPS fulfills its responsibility in ensuring the compliance of Sharia hotel operations with the principles outlined in DSN-MUI Fatwa No. 108 of 2016 on Sharia Tourism. This study employs a qualitative approach using a case study method. Data were collected through interviews, direct observations, and analysis of relevant documents. Interviews were conducted with DPS members, Sharia hotel management, and other related stakeholders to gain a deep understanding of DPS oversight implementation. The findings reveal that DPS plays a crucial role in monitoring the implementation of Sharia principles in Sharia hotels. However, challenges such as limited resources and uneven understanding among DPS members hinder effective oversight. The study highlights the need for capacity building and better coordination between DPS, hotel management, and other stakeholders to enhance accountability and ensure compliance with DSN-MUI fatwas. Effective DPS oversight can improve service quality, public trust, and the sustainability of Sharia hotel operations.